Políticas de comunicação, democracia (RECIIS, 2010)
The free access, full text version in English of this paper was translated from the original in Portuguese or Spanish and is currently undergoing a Creative Commons licensing process and a second text style review that are now a part of Reciis' commitment to editorial excellence. The latest version, which will be released under the Creative Commons License and also in PDF format, will be available by November 30th.